Técnica socket shield: análise da distribuição de tensões - Neves, Ricardo Guimarães (2019)
Objective: To compare, by means of a three-dimensional finite element method, the influence of the Socket Shield (SS) technique on the stress distribution on peri-implant bone, implants and prosthetic componentes in comparison to other techniques for rehabilitation of anterosuperior tooth loss. Material and method: Geometrical models of a implant-supported central incisor were designed by simulating three different placement techniques: SS group, with a 2,5mm-thick radicular dentine fragment positioned within the buccal alveolar wall and the implant; Heterogeneous Graft (HG) group, with a heterogenous bovine bone grafting material placed within the buccal alveolar wall and the implant; and control group, with the entire implant in contact with bone tissue of a healed alveolar ridge. Models were loaded with 100 N on the palatal surface (angled to 45º in relation to tooth long axis to simulate maximum intercuspation) and 25 N perpendicular to the incisal edge (to simulate "edge-to-edge” contact). Maximum stresses (tensile, shear and compressive) and displacement in the bone tissue including the alveolar crest cortical plate, trabecular bone, root dentin and bone graft were analyzed. Von Mises equivalent stress was evaluated for the implants and prosthetic components. Results: Higher stress values for bone tissue were observed for SS and HG groups in comparison to control. Stress values within groups were not significant different for dentin fragment, bone graft, implant and prosthetic components. Conclusion: Stress concentration in the bone tissue was higher for SS, followed by HG and control group.